2021
DOI: 10.1186/s12889-021-11366-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing smoking behaviour of online ride-hailing drivers in China: a cross-sectional analysis

Abstract: Background Online ride-hailing is a fast-developing new travel mode. However, tobacco control policies on its drivers remain underdeveloped. This study aims to reveal the status and determine the influencing factors of ride-hailing drivers’ smoking behaviour to provide a basis for the formulation of tobacco control policies. Methods We derived our cross-sectional data from an online survey of full-time ride-hailing drivers in China. We used a surve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Our results suggest that participants' smoking status is a significant determinant of health literacy. The relationship between unhealthy lifestyles, such as smoking, and health literacy has been widely reported in different populations from youth to elderly [39][40][41][42]. Tobacco use is one of the most serious health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that participants' smoking status is a significant determinant of health literacy. The relationship between unhealthy lifestyles, such as smoking, and health literacy has been widely reported in different populations from youth to elderly [39][40][41][42]. Tobacco use is one of the most serious health risks.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the smoking rate of ride-hailing drivers was high. Sociodemographic and work-related characteristics and health-related factors affected their smoking behavior [30].…”
Section: Discussionmentioning
confidence: 99%
“…81.2% of respondents said they wanted to quit smoking because of their own motivation, and 58.7% of respondents wanted to quit smoking because of information obtained from mass media such as newspapers. The motivation to stop smoking in this study were respondents who had tried to quit smoking and the motivation measuring scale was in the form of a questionnaire to determine whether the level of motivation of respondents was high, medium or low [22].…”
Section: Discussionmentioning
confidence: 99%